2022
DOI: 10.21203/rs.3.rs-2312435/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Artificial Neural Network-based Radiomics model for Predicting Radiotherapy response of Advanced Esophageal Squamous Cell Carcinoma patients: A multi-center Study

Abstract: Radiotherapy benefits patients with advanced esophageal squamous cell carcinoma (ESCC) on symptom relief and long-term survival. Contrarily, a substantial proportion of ESCC patients have not benefited from radiotherapy. This study aimed to establish and validate an artificial neural network-based radiomics model for the pre-treatment predicting radiotherapy response of advanced ESCC by using integrated data combined with feasible baseline characteristics of computer tomography. The 248 patients with advanced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Arti cial intelligence (AI) and radiomics has the potential to revolutionize the eld of HCC therapy 6,7 . They can be employed to identify "hidden" patterns or to analyze a large number of variables simultaneously [8][9][10][11] . For example, recent studies showed that multiphase computed tomography (CT) can be employed to evaluate the progression of liver brosis or the severity of chronic liver disease [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Arti cial intelligence (AI) and radiomics has the potential to revolutionize the eld of HCC therapy 6,7 . They can be employed to identify "hidden" patterns or to analyze a large number of variables simultaneously [8][9][10][11] . For example, recent studies showed that multiphase computed tomography (CT) can be employed to evaluate the progression of liver brosis or the severity of chronic liver disease [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%